PERANCANGAN KOLEKSI CONVERTIBLE FASHION MENGGUNAKAN TEKNIK MANIPULASI KOMPONEN UNTUK BRAND MICHELLE ALVINA - Alvina, Michelle; Handayani, Rahayu Budhi (Jurnal VICIDI, 2020)
This design, specifically targeted to Indonesian women, is made for Michelle Alvina’s new collection in respond to business opportunity in clothing that can be worn in several ways - called transformable or convertible fashion. This design is proposed to address some problems in the fashion industry. One of the problems is a travellers’ problem in choosing outfits to avoid overweight luggage. Another problem is how the people like to experiment with their usual clothing, which can be difficult as they are not as easy as convertible clothing to transform it to the other shape. After conducting research using two methods; quantitative (survey-based method) and qualitative (interview to expert and extreme user also literature). Michelle Alvina hopes to address this problem as well by giving alternative Desains for a piece of ready-to-wear clothing while using component manipulation technique. Michelle Alvina Spring/ Summer 2017 convertible fashion collection, titled “Gladiolus”, is made after conducting research and interviews on expert and extreme users. This collection includes five ready-to-wear designs from the production process to the end products. Inspired by the shape and meaning of gladiolus flowers, and combined with its minimalist interior, this collection brings out elegant, modern and feminine style, well suited for women aged 22 to 28 years old.